Centering decriminalization of suicide in low – and middle – income countries on effective suicide prevention strategies - Ochuku, Brenda K.; Johnson, Natalie E.; Osborn, Tom L.; Wasanga, Christine M.; Ndetei, David M. (Frontiers in Psychiatry, 2022)
Globally, over 800,000 people die by suicide every year. For every one completed suicide, 20 more attempts have been made. As previous attempts are one of the strongest predictors of future suicide, help-seeking in moments of crisis, particularly after an attempt, may have important implications for suicide prevention. Unfortunately, the criminalization of suicide in several countries hinders help-seeking, increases the stigmatization of those who attempt suicide and obstructs the accurate tracking of suicides. Here, we highlight the negative effects of suicide criminalization and discuss evidence-based strategies for suicide prevention such as means restriction, improved mental health literacy and access to psychosocial support, and responsible media coverage of suicides.